Attitudes and behaviors of chiropractic interns toward occupational history taking - Madigan, Dana (J Chiropr Educ, 2020)
OBJECTIVE: This study uses a pre- and post-training program evaluation of chiropractic interns to (1) describe changes in their frequency of occupational history taking before and after a 1-hour training and (2) to document the attitudes and beliefs regarding occupational health and history taking. METHODS: All chiropractic interns at 1 clinic location completed questionnaires assessing their attitudes and perceptions regarding documenting the occupational history of their patients each trimester they were enrolled in the study. Each intern enrolled in the study for 2 or more trimesters participated in a 1-hour-long training session on taking an occupational history. The supervising clinician independently evaluated charting behaviors of interns for the duration of the study. RESULTS: The supervising clinician assessed 20 interns' level of documenting occupational history for 202 new patient or reexamination visits. A majority of interns (85% at baseline) were interested in occupational health, and 80% believed that occupational history taking was “very important.” Intern charting behaviors increased after training related to documentation of past occupation (62.9% from 32.4%) and relating the chief complaint to work (59.7% from 30.0%). Detailed occupational history taking remained low throughout the study but demonstrated a doubling in documentation after training (16.1% from 8.6%). CONCLUSION: Chiropractic interns and clinicians should be adequately trained in occupational health history documentation practices as they are likely to care for work-related injuries. Short training modules appear to be effective in demonstrating small changes in documentation related to occupational history taking.